Diet-Induced Obesity Disturbs Microglial Immunometabolism in a Time-of-Day Manner - Milanova, Irina V.; Kalsbeek, Martin J. T.; Wang, Xiao-Lan; Korpel, Nikita L.; Stenvers, Dirk Jan; Wolff, Samantha E. C.; de Goede, Paul; Heijboer, Annemieke C.; Fliers, Eric; la Fleur, Susanne E.; Kalsbeek, Andries; Yi, Chun-Xia (Frontiers in Endocrinology, 2019)
Background: Disturbance of immunometabolic signaling is a key process involved in the progression of obesity. Microglia– the resident immune cells in the brain, initiate local immune responses. It is known that hypercaloric diets lead to microglial activation. Previously, we observed that hypothalamic microglial cells from mice fed high-fat diet (HFD) lose their day/night rhythm and are constantly activated. However, little is known about daily rhythmicity in microglial circadian, immune and metabolic functions, either in lean or obese conditions. Therefore, we hypothesized that HFD disturbs microglial immunometabolism in a day/night-dependent manner. Methods: Obesity was induced in Wistar rats by feeding them HFD ad libitum for the duration of eight weeks. Microglia were isolated from HFD- and chow-fed control animals at six time points during 24h (every four hours starting 2h after lights on, i.e. Zeitgeber Time 2 (ZT2)). Gene expression was evaluated using quantitative RT-PCR. JTK_Cycle software was used to estimate daily rhythmicity. Statistical analysis was performed with two-way ANOVA test. Results: Consumption of the obesogenic diet resulted in a 40 g significantly higher body weight gain in week eight, compared to chow diet (p<0.0001), associated with increased adiposity. We observed significant rhythmicity of circadian clock genes in microglia under chow conditions, which was partially lost in diet-induced obesity (DIO). Microglial immune gene expression also showed time-of-day differences, which were disrupted in HFD-fed animals. Microglia responded to the obesogenic conditions by a shift of substrate utilization with decreased glutamate and glucose metabolism in the active period of the animals, and an overall increase of lipid metabolism, as indicated by gene expression evaluation. Additionally, data on mitochondria bioenergetics and dynamics suggested an increased energy production in microglia during the inactive period on HFD. Finally, evaluation of monocyte functional gene expression showed small or absent effect of HFD on peripheral myeloid cells, suggesting a cell-specific microglial inflammatory response in DIO. Conclusions: An obesogenic diet affects microglial immunometabolism in a time-of-day dependent manner. Given the central role of the brain in energy metabolism, a better knowledge of daily rhythms in microglial immunometabolism could lead to a better understanding of the pathogenesis of obesity.